2007
DOI: 10.2135/cropsci2006.04.0243
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Variation for Three Physiological Traits Affecting Drought Tolerance in Soybean

Abstract: Three physiological traits that may affect performance of soybean [Glycine max (L.) Merr.] when soil water availability is limiting are (i) water use efficiency (WUE), (ii) regulation of whole plant water use in response to soil water content, and (iii) leaf epidermal conductance (ge) when stomata are closed. Six soybean plant introductions (PIs), eight breeding lines derived from them, and nine cultivars were compared for variability in these three traits during vegetative growth in two greenhouse studies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 39 publications
(70 reference statements)
10
132
0
1
Order By: Relevance
“…However, there are a few reports of genetic variation within a species for the threshold value of soil water where transpiration decreases. Hufstetler et al (2007) compared the threshold among 21 soybean genotypes grown on a sandy soil and found significant genetic differences. Devi et al (2009) Belko et al (2012).…”
Section: Minimising Water-deficit Limitationmentioning
confidence: 99%
“…However, there are a few reports of genetic variation within a species for the threshold value of soil water where transpiration decreases. Hufstetler et al (2007) compared the threshold among 21 soybean genotypes grown on a sandy soil and found significant genetic differences. Devi et al (2009) Belko et al (2012).…”
Section: Minimising Water-deficit Limitationmentioning
confidence: 99%
“…Mian et al [19] reported that WUE is one of the physiological traits associated with drought tolerance in soybean. Hufstetler et al [11]. noted that WUE was significantly and negatively correlated with leaf epidermal conductance during vegetative growth in a study of 12 bean varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited water resource, a crop with a higher WUE can produce superior biomass and/or economic yield [7]. The level of WUE varies in different crops such as rice, peanut, cowpea, cotton, sorghum, barley, wheat and soybean [4,7,[10][11][12]. The WUE is commonly evaluated at 3 levels: single leaf (the ratio of net CO 2 assimilation to transpiration of a single leaf) [7], plant [13] and population [4].…”
mentioning
confidence: 99%
“…It is considered that higher IWUE values provide an indication of improved drought tolerance because varieties with high IWUE values are better able to assimilate carbon at low stomatal conductance and hence attain a greater yield using less water than other varieties. Genetic variation has been observed in soybean with regard to the amount of dry matter produced per given amount of water (Hufstetler et al, 2007). Moreover, soybean genotypes with a quick recovery after drought stress were more productive than genotypes with slower recovery (Hufstetler et al, 2007).…”
Section: Water Use Efficiencymentioning
confidence: 99%